PERLINDUNGAN HAK-HAK KONSUMEN TERHADAP PASAL 480 KITAB UNDANG-UNDANG HUKUM PIDANA MENGENAI PENADAHAN - Desmawaty Romli; Junaidi (Bajang Institute, 2021)
The criminal act of detention as regulated in Article 480 of the Criminal Code, in which the detention element in the article is very easy to ensnare anyone who receives the proceeds of crime with an intentional element (dolus), which means that the perpetrator of the detention can be deemed appropriate must be can suspect the origin of goods from crime and it is difficult to prove that the collector really knows about it (the origin of the goods) As for the relationship with consumer protection related to this case, it can be seen in Article 4 of Law Number 8 of 1999 concerning Consumer Protection which describes consumer rights. Detention based on Article 480 of the Criminal Code is combined between deliberate offense (knowing) that an item originates from a crime and an offense of negligence (culpa) marked with the words